Afrikaans as symptom-formation: A Freudian reading of "Afrikaner" history - van Kyk, Johan; Voice, Paul (PINS-Psychology in Society, 2025)
In this paper a few ideas and positions will be sketched for a psychoanalytical reading of the Afrikaner. These ideas represent part of a more extensive project in this area on which we are working. Our discussion is premised on the idea that the term "Afrikaner" has a shifting denotation and the study of it should entail a careful analysis of the different discursive contexts of which it is a part. The meaning of the term, like any other, is conditioned by changes which take place at the level of the economic and the ideological. In this sense the Afrikaner is a discursive and ideological construct (1). In another sense, as we will show, the fabrication of a collective identity, beginning with the activities of the GRA (Genootskap van Regte Afrikaners; The Association of Real Afrikaners) in the late 1800s, fashioned a past which relates to an original lawlessness and omnipotence. We briefly trace the way in which this lawlessness was threatened with the arrival of the British at the Cape in 1795. We contrast the lawless, father-orientated perspective of the colonists with the modern recognition of the world as object which is determined by natural laws. Here we employ a number of Freudian concepts whose use suggests that the preoccupation with the Afrikaans language, with race and nation can be read as a symptom-formation which relates to the Afrikaner nationalist’s melancholia - a longing for a lost omnipotence.